2013
DOI: 10.2967/jnumed.112.118612
|View full text |Cite
|
Sign up to set email alerts
|

64Cu-DOTA-Trastuzumab PET Imaging in Patients with HER2-Positive Breast Cancer

Abstract: The purpose of this study was to determine the safety, distribution, internal dosimetry, and initial human epidermal growth factor receptor 2 (HER2)-positive tumor images of 64 Cu-DOTA-trastuzumab in humans. Methods: PET was performed on 6 patients with primary or metastatic HER2-positive breast cancer at 1, 24, and 48 h after injection of approximately 130 MBq of the probe 64 Cu-DOTA-trastuzumab. Radioactivity data were collected from the blood, urine, and normal-tissue samples of these 6 patients, and the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(172 citation statements)
references
References 26 publications
5
151
1
3
Order By: Relevance
“…In both studies, the best time for imaging was 48 h after tracer injection. However, the results were different; the coinjection of 45 mg of trastuzumab enabled better visualization of liver metastases (35), whereas the results obtained with the administration of only the radiotracer were suboptimal because of a higher liver background (34). Interestingly, both studies compared 64 Cu-trastuzumab PET/CT with 18 F-FDG PET/CT, with a maximum of 13 d in between, and showed that some lesions could be detected only with 64 Cu-trastuzumab PET/CT.…”
Section: Preclinical Settingmentioning
confidence: 96%
See 1 more Smart Citation
“…In both studies, the best time for imaging was 48 h after tracer injection. However, the results were different; the coinjection of 45 mg of trastuzumab enabled better visualization of liver metastases (35), whereas the results obtained with the administration of only the radiotracer were suboptimal because of a higher liver background (34). Interestingly, both studies compared 64 Cu-trastuzumab PET/CT with 18 F-FDG PET/CT, with a maximum of 13 d in between, and showed that some lesions could be detected only with 64 Cu-trastuzumab PET/CT.…”
Section: Preclinical Settingmentioning
confidence: 96%
“…The study also highlighted the importance of the mass of administered protein, concluding that in trastuzumab-naive patients, a higher mass of (nonradiolabeled) trastuzumab (50 mg) enabled better distribution of the tracer into the metastatic lesions. In addition, trastuzumab was also labeled with 64 Cu in studies of both early and advanced HER2-positive BC (34,35). In both studies, the best time for imaging was 48 h after tracer injection.…”
Section: Preclinical Settingmentioning
confidence: 99%
“…In ersten Tierexperimenten bewiesen Smith-Jones et al [61] sowohl die Mög-lichkeit der nichtinvasiven Messung der HER2-Expression mit einem 68 Ga-markierten Fragment von Trastuzumab ll als auch die therapieinduzierte Ände-rung der HER2-Expression. In ersten klinischen PET-CT-Studien mit 64 Cu-DOTA-Trastuzumab konnte die 64 Cu-DOTA-Trastuzumab-PET-CT sowohl den Primärtumor als auch Metastasen mit hoher Sensitivität detektieren und hat somit das Potenzial, HER2-zielgerichtete Therapiestrategien zu optimieren [62].…”
Section: Mp-pet-mrtunclassified
“…Однако рост опухоли в ГМ, а также последствия нейрохирургических вмешательств и об-лучения мозга могут нарушить гематоэнцефалический барьер и «открыть» доступ для системных препаратов в опухоль. Эта концепция была подтверждена в ряде исследований [26,27]. Кроме того, несколько клини-ческих исследований показали, что сочетание химио-терапии с трастузумабом повышает выживаемость даже после развития метастазов в ГМ [28,29].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified